2017
DOI: 10.3892/ol.2017.7424
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miRNA‑15a and miRNA‑16 promote tumor proliferation in multiple myeloma by increasing CABIN1 expression

Abstract: Abstract. Multiple myeloma (MM) is a malignant disorder characterized by the neoplastic growth of plasma cells in the bone marrow. MicroRNAs (miRNAs/miRs) modulate key regulatory cell pathways via their influence on target genes, and may serve a crucial function in tumorigenesis. Previous studies have indicated that the downregulation of miR-15a and miR-16 contributes to MM pathogenesis. However, the functional mechanisms of miR-15a and miR-16 in MM remain unclear. In the present study, potential target sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
0
21
0
1
Order By: Relevance
“…S6). Bcl2, Vegfa, Tab3, and Cabin1, previously reported to be direct miR15-a/16-1 targets in multiple myeloma or CLL, were not differentially expressed in MYCxMIR tumors (17,(32)(33)(34). However, Bcl2 was not generally expressed in Vk*MYC tumors, with appreciable expression in 3 of 45 de novo Vk*MYC compared with 3 of 16 transplant and 3 of 18 Vk*MYCxMIR and Vk*MYCxMDR tumors, where the expression levels were 2-to 4-fold higher.…”
Section: Loss Of the Mir15a/mir16-1 Cluster Induces Myeloma Cell Prolmentioning
confidence: 84%
“…S6). Bcl2, Vegfa, Tab3, and Cabin1, previously reported to be direct miR15-a/16-1 targets in multiple myeloma or CLL, were not differentially expressed in MYCxMIR tumors (17,(32)(33)(34). However, Bcl2 was not generally expressed in Vk*MYC tumors, with appreciable expression in 3 of 45 de novo Vk*MYC compared with 3 of 16 transplant and 3 of 18 Vk*MYCxMIR and Vk*MYCxMDR tumors, where the expression levels were 2-to 4-fold higher.…”
Section: Loss Of the Mir15a/mir16-1 Cluster Induces Myeloma Cell Prolmentioning
confidence: 84%
“…Downregulation of miRNA-16 has been observed in oral squamous carcinoma and multiple myeloma. 9,10 Overexpression of miRNA-16 inhibited tumor growth in oral squamous carcinoma by targeting Wnt/β-catenin signaling pathway. In addition to the direct roles in cancer development and progression, miRNA-16 also participates in the development of drug resistance of cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We reported that MORT was also downregulated in MCL and its overexpression inhibited MCL cell proliferation and promoted MCL cell apoptosis possibly by upregulating miRNA-16, which is a wellestablished tumor suppressor miRNA in different types of cancers. 9,10…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, only the miR-17-92 cluster and miR-32 were up-regulated in MM cell lines and MM samples in comparison with MGUS or normal PCs, which suggest their possible implication in malignant transformation of MGUS to MM. 62 Furthermore, it was demonstrated that miRNAs could affect crucial cellular pathways of MM cells: miR-19b/20a regulates proliferation, migration, and apoptosis 59 ; miR-20a regulates the proliferation and migration by modulating the PTEN/PI3K/AKT signaling pathway 68 ; miR-410 promotes cell proliferation, cell cycle progression, and inhibits apoptosis, 69 over expression of miR-1271 inhibited proliferation and promoted apoptosis 26 ; miR-29b controls the methylation profile 26 ; miR-29b leads to induction of SOCS-1 expression by promoter demethylation and negatively regulates the migration 31 ; overexpression of miR33b decreased MM cell viability, migration, colony formation, and increased apoptosis and sensitivity to MLN2238 treatment 41 ; upregulation of miR-15a and miR-16 inhibits the proliferation 43 ; miR-22 inhibits LIG3-dependent DNA repair inducing DNA damage and apoptosis 63 ; miR-324-5p regulates stemness, pathogenesis, and sensitivity to bortezomib. 40 To avoid being degraded, extracellular miRNAs bind to proteins in urine, saliva, plasma, serum, and other body fluids, or are protected by apoptosis bodies, particles, exosomes, and tiny vesicles.…”
Section: Micrornas and MMmentioning
confidence: 99%
“…Furthermore, it was demonstrated that miRNAs could affect crucial cellular pathways of MM cells: miR‐19b/20a regulates proliferation, migration, and apoptosis; miR‐20a regulates the proliferation and migration by modulating the PTEN/PI3K/AKT signaling pathway; miR‐410 promotes cell proliferation, cell cycle progression, and inhibits apoptosis, over expression of miR‐1271 inhibited proliferation and promoted apoptosis; miR‐29b controls the methylation profile; miR‐29b leads to induction of SOCS‐1 expression by promoter demethylation and negatively regulates the migration; overexpression of miR33b decreased MM cell viability, migration, colony formation, and increased apoptosis and sensitivity to MLN2238 treatment; upregulation of miR‐15a and miR‐16 inhibits the proliferation; miR‐22 inhibits LIG3‐dependent DNA repair inducing DNA damage and apoptosis; miR‐324‐5p regulates stemness, pathogenesis, and sensitivity to bortezomib …”
Section: Micrornas and MMmentioning
confidence: 99%